Evaluación del estado de madurez del babaco (carica pentagona) en postcosecha con la aplicación de tres dosis de etileno, en dos estados de cosecha a tres temperaturas de almacenamiento. provincia de Cotopaxi - Chile Tupiza, Mayra Geovanna (2013)
The babaco (Carica pentagona) it is one of the promissory products of export so it is considered as exotic fruit, it is an Andean species it originally from Ecuador. The investigative work was carried out in the Latacunga canton, Eloy Alfaro parish, Cotopaxi province. The laboratory works were carried out under conditions of ambient temperature 4oC with a relative humidity of the 75%, 8oC with a relative humidity of 90%, and 22oC with a relative humidity of 50%. factorial arrangement 3x2x3 implemented in a was used (D.B.C.A), with eighteen treatments and three repetitions, the test of Tukey was applied (5%), the variables that were analyzed were: Color of the epidermis, loss of Weight (g), Stability of the fruit (lbfxcm2-1), soluble solids (oBrix), Acidity, incidence of plagues....